2018
DOI: 10.21037/jtd.2018.05.148
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant mitral valve surgery in patients with moderate ischemic mitral regurgitation undergoing coronary artery bypass grafting

Abstract: The addition of a concomitant MV surgery increased the risk of early mortality and complications in patients with moderate iMR undergoing CABG. In long-term clinical and echocardiographic outcomes, a concomitant MV surgery seemed to confer no significant clinical benefits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 27 publications
0
12
1
1
Order By: Relevance
“…The length of hospital stays did not differ significantly between groups. These results partially contradict Kim and colleagues’ study [ 20 ]. They reported higher neurological and cardiac complications, low cardiac output, and mortality in CABG and MVR patients.…”
Section: Discussioncontrasting
confidence: 94%
See 1 more Smart Citation
“…The length of hospital stays did not differ significantly between groups. These results partially contradict Kim and colleagues’ study [ 20 ]. They reported higher neurological and cardiac complications, low cardiac output, and mortality in CABG and MVR patients.…”
Section: Discussioncontrasting
confidence: 94%
“…EF was significantly lower in CABG with MVR patients; moreover, these patients had a higher prevalence of LV dilatation. Kim and associates [ 20 ] reported comparable characteristics between patients with CABG alone versus CABG and mitral repair. However, patients with mitral repair had a significantly lower EF.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, several studies including a 2009 meta-analysis [15] have reported no survival benefit to adding MV repair to CABG (95% confidence interval [CI] 0.90–1.14, P = .73) for patients with IMR. Byung et al [6] reported that during a median follow-up of 78.0 months, the incidence of all-cause mortality was 232 (5.8% per year) in CABG-only group and 54 (7.5% per year) in CABG + MV surgery group ( P = .12), which suggests that a concomitant MV surgery seems to confer no significant clinical benefits. This study also points that CABG plus MVR group does have a significantly increased rate of neurological events (14 events) than CABG-only group (4 events; P = .02).…”
Section: Discussionmentioning
confidence: 99%
“…MR is strictly quantified according to European Society of Echocardiography diagnostic criteria. [6]…”
Section: Methodsmentioning
confidence: 99%
“…FIGURE 3: Forest plot comparing risk of mortality between two groups CABG: Coronary artery bypass surgerySources: References[7,8,12,[15][16][17][18]20,21] …”
mentioning
confidence: 99%